Strengthening Rural Economy through Regional Development Planning Approach in Sarawak - Daniel Ugih, Echoh; Novel, Lyndon; Suhana, Saad; Sarmila, Md Sum; Zaimah, Ramli (Human Resource Management Academic Research Society, 2018)
Rural development often linked with regional development and both are considered as detached entities in regional development efforts whereby they are mutually dependent on their development. Both of these developments are tied together by various types of rural-urban-regional linkages and the understanding of the reciprocal relationship behind these areas and consideration of this relationship in regional development strategies are very effective in the development of both areas. This paper seeks to discuss the rural development strategies in Sarawak through the implementation of regional development planning approaches such as the Sarawak Corridor of Renewable Energy (SCORE). For the purpose of data collection, this paper utilized qualitative research method of secondary data analysis of previous studies which did by government agencies and researchers. Therefore, the content analysis was used to analyze the data. The study found that the regional development policies in Sarawak have changed the rural economy by developing physical, social and economic programs under the corridor economic projects.